Carbon Nanotubes, Carbon Fibers and Carbon Nanofibers for Natural Rubber Applications - Tahir, Hairani (2009)
Nanomaterials are well known to be used as reinforcing fillers. With its high surface area, addition of small amount of nanomaterials in the polymer matrix would increase the strength of the composite material. Carbon nanotubes (CNTs), carbon fibers (CFs) and carbon nanofibres (CNFs) are among the nanomaterials that are commonly used as fillers to improve the mechanical properties. These nanomaterials have excellent mechanical and thermal characteristics. The good characteristics of natural rubber such as heat built up, hysteresis, impact, and tensile strength, flexing and damping capability on service were expected to be enhanced when added with nanomaterials such as carbon nanotubes. The other method used to synthesize nanomaterials are based on laser ablation and arc discharge which limit the production size and produces a large amount of impurities. Chemical Vapor Deposition (CVD) was selected to encounter the problems mentioned. However, the most common problem faced in the production of nanocomposites is the blending of the matrix with the nanomaterial. This research project aims to find the suitable method to incorporate different nanomaterials with the natural rubber matrix. CNTs, CFs and CNFs were synthesized using the Floating Catalyst Chemical Vapor Deposition (FC-CVD) method. Viscosity-stabilized natural rubber, SMRCV60, was used as the matrix. The blends were prepared using the solvent casting method. Test samples were then prepared using hot press. The nanomaterials are successfully synthesized by the Floating Catalyst Chemical Vapor Deposition (FC-CV) method. In this study, the production condition of pure CNTs has been fixed at reaction temperature 850° C with the hydrogen flow rate of 300 ml/min and reaction time 30 minutes. The nanomaterials then were used to prepare a rubber nanocomposites using solvent casting method. The tensile property shows that CNTs possess the highest strength with 1.21 MPa at 7% composition. The composite which contains 5% CNFs gave the highest strain at about 12.2% elongation. With 5 % CFs filling in the matrix, 7.75% elongation was achieved. From DMTA analysis, the damping characteristic, tan d proved the theoretical prediction of rubber nanocomposites, as the amount of filler increases the nanocomposites become rigid which is very significant from the storage modulus plot. The natural rubber nanocomposites possess the best tensile and thermal properties even without extensive purification on the nanomaterials produced and without any pretreatment on the natural rubber used.